INSIDEN HEWAN QURBAN SEBAGAI VEKTOR PENULAR PENYAKIT CACING HATI (FASCIOLOSIS) DI SURABAYA - Freshinta Jellia Wibisono; Rondius Solfaine (JURNAL KAJIAN VETERINER, 2019)
Qurban animals slaughtering in ied qurban commonly increases the demand of livestock and thusautomatically escalate the livestock traffic. as well as the level of prevention against transmission of diseases. The aim of this research is to determine the possibility of qurban animals as vector of fasciolosis transmission in Surabaya through the prevalence of fasciolosis among qurban animals and the magnitude of the economic losses due to the damage of the liver. Research was performed during ied qurban 1436h on september 24th 2015 upon a total Samples of 384 qurban animals. Fasciolosis was taken as a diagnoseBased on the findings of fasciolain liver during inspection and their eggs in the faeces upon laboratory examination. overall, the prevalence of fasciolosis among all types of qurban animals in Surabaya in 2015 based on liver inspection was 18,5%, meanwhile fecal examination was 15,1%. In detail, qurban cattle showed 28,1% and 24.6%, whereas goats revealed 10,8% and 7.5% prevalences of fasciolosis due to the findings of fasciola on liver inspection and eggs on faeces examination respectively. Economic losses due to liver damage was calculated around Rp. 6.962.362.500,-.